Effect of varieties and growing environments on tuber yield, nutritional and process quality of potato grown in bale highlands, south eastern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2018)
The highland of Bale is known with potato production, but post harvest quality of the crop is not emphasized yet. Therefore, this study was conducted to evaluate six potato varieties with the objective of assessing the effect of varieties and growing on tuber nutritional and process quality of potato grown in Sinana and Dinsho highlands of Bale. The experiment was laid out in randomized complete block design with three replications. The varieties showed highly significant (P